2006
DOI: 10.1080/00207450500403371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electromagnetic Fields Emitted by Cellular Phones on the Latency of Evoked Electrodermal Activity

Abstract: The widespread use of cellular phones raises the question of their possible adverse biological effects, especially on the central nervous system (CNS). Therefore, the authors examined the effect of electromagnetic fields emitted by cellular phones (CPEMFs) on the evoked neuronal activity of CNS relating to generation and representation of electrodermal activity (EDA), an index of sympathetic nervous system activity. EDA (skin resistance response; SRR) latency was lengthened approximately 200 ms with CPEMFs exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…With regard to latency, our results are not in accordance with those previously reported in a study by Esen and Esen, in which latency was found to be lengthened by approximately 200 ms under exposure to the EMFs of a mobile phone (Esen and Esen, 2006). It should be noted that there are differences in the methodological approach between our experiment and that of Esen and Esen.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…With regard to latency, our results are not in accordance with those previously reported in a study by Esen and Esen, in which latency was found to be lengthened by approximately 200 ms under exposure to the EMFs of a mobile phone (Esen and Esen, 2006). It should be noted that there are differences in the methodological approach between our experiment and that of Esen and Esen.…”
Section: Discussioncontrasting
confidence: 99%
“…With regard to EDA, one study showed a shorter latency of EDA under exposure to 900 MHz (Esen and Esen, 2006). In studies involving subjects hypersensitive to EMF, the results showed no effect of EMF exposure on the latency of the amplitude, the number of peaks of SCR (Wilén et al, 2006) or on the level of skin conductance (Eltiti et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Other studies were excluded from the review because the authors did not meet criteria (a), (b) and (c) [Ozturan et al, 2002;Bak et al, 2003;Oysu et al, 2005;Pau et al, 2005], whereas Arai et al [2003] did not satisfy criteria (a) and (c). The study of Sievert et al [2005] did not meet criteria (a) and (b), while criteria (b) and (c) were not satisfied in experiments carried out by Eulitz et al [1998] and Esen and Esen [2006]. Moreover, the study by Hietanen et al [2000] did not satisfy criteria (c) and (d).…”
Section: Literature Search and Selectionmentioning
confidence: 74%